Pengaruh Kompensasi Finansial Dan Lingkungan Kerja Fisik Terhadap Turnover Intention Karyawan Melalui Kepuasan Kerja Sebagai Variabel Mediasi Pada Karyawan RS. Bhakti Husada Bekasi - Kartika, Rahmawati Dwi; Rezeki, Fitri (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Human resource management consists of a series of actions to train, assess, compensate employees, manage work relations and employee health and safety, and how the company can survive over the long term. A company cannot operate without employees. Apart from recruiting employees, companies must also consistently try to improve employee abilities through training and development activities, organizing work methods, providing appropriate compensation, and creating a good work environment. The purpose of this research is to determine the effect of financial compensation and the physical work environment on employee turnover intention through job satisfaction as a mediating variable for employees at RS.Bhakti Husada Bekasi. This research used quantitative methods with a sample size of 67 respondents with a population of 203 employees at Bhakti Husada Bekasi Hospital. This research processes data using SmartPLS 3.0 software and collects data via Google from. The results of this research show that financial compensation has a significant effect on employee turnover intention, the physical work environment has no significant effect on employee turnover intention, job satisfaction has no significant effect on employee turnover intention, financial compensation has a significant effect on job satisfaction, financial compensation has no significant effect on satisfaction. work which is mediated by employee turnover intention and cannot influence the physical work environment, nor can it have a significant effect on job satisfaction which is mediated by employee turnover intention.